Novel N-Acyl Homoserine Lactone-Degrading Bacteria Isolated From Penicillin-Contaminated Environments and Their Quorum-Quenching Activities - Kusada, Hiroyuki; Zhang, Yu; Tamaki, Hideyuki; Kimura, Nobutada; Kamagata, Yoichi (Frontiers in Microbiology, 2019)
N-Acyl homoserine lactones (AHLs) are signaling molecules used in the quorum sensing (QS) of Gram-negative bacteria. Some bacteria interfere with the QS system using AHL-inactivating enzymes, commonly known as quorum-quenching (QQ) enzymes. We have recently isolated a new QQ bacterium showing high resistance to multiple β-lactam antibiotics, and its QQ enzyme (MacQ) confers β-lactam antibiotic resistance and exhibits QQ activities. This observation suggests the possibility of isolating novel QQ bacteria from β-lactam antibiotic-resistant bacteria. In this direction, we attempted to isolate penicillin G (PENG)-resistant bacteria from penicillin-contaminated river sediments and activated sludge treating penicillin-containing wastewater and characterize their QQ activities. Of 19 PENG-resistant isolates, six isolates showed high QQ activity toward a broad range of AHLs, including AHLs with 3-oxo substituents. Five of the six AHL-degraders showed AHL-acylase activity and hydrolyzed the amide bond of AHLs, whereas the remaining one strain did not show AHL-acylase activity, suggesting that this isolate may likely possess alternative degradation mechanism such as AHL-lactonase activity hydrolyzing the lactone ring of AHLs. The 16S rRNA gene sequence analysis results categorized these six AHL-degrading isolates into at least five genera, namely, Sphingomonas (Alphaproteobacteria), Diaphorobacter (Betaproteobacteria), Acidovorax (Betaproteobacteria), Stenotrophomonas (Gammaproteobacteria), and Mycobacterium (Actinobacteria); of these, Mycobacterium sp. M1 has never been known as QQ bacteria. Moreover, multiple β-lactam antibiotics showed high minimum inhibitory concentrations (MICs) when tested against all of isolates. These results strongly demonstrate that a wide variety of β-lactam antibiotic-resistant bacteria possess QQ activities. Although the genetic and enzymatic elements are yet unclear, this study may infer the functional and evolutionary correlation between β-lactam antibiotic resistance and QQ activities.